Pancasila and the Politics of Representation: From Quotas to Quality in Post-Reformasi Indonesia (2019-2022) - Prasetyo, Ardian; Permana, Aditya; Mulya, Debora Pruyanka (Badan Pembinaan Ideologi Pancasila, 2025)
Gender inequality remains a significant barrier to democratic quality in Indonesia, particularly in parliamentary representation. Although women’s political participation is constitutionally guaranteed, their presence in parliament reached only 20.35% in 2020, below the 30% global recommendation (IPU, 2020). This study explores how political party culture affects women’s representation using the Feminist Institutionalism (FI) framework combined with Pancasila values. It examines both formal institutions, i.e. electoral quotas, internal party rules, and women’s roles in party decision-making, and informal institutions like religious norms, gendered moral expectations, and patron-client traditions. The findings reveal that while formal mechanisms supporting women exist, their implementation is often symbolic, lacking meaningful impact. Informal institutions still dominate political life, reinforcing masculine leadership ideals and limiting women’s access to power. Practices such as political dynasties and patronage systems further marginalize women, especially those without elite backgrounds or financial capital. Viewed through Pancasila, there is a clear gap between foundational national ideals and political realities. While Pancasila promotes justice and equality, entrenched patriarchal norms continue to shape political participation. The study concludes that deeper cultural transformation is needed to align political party practices with the inclusive spirit of Pancasila.